ANALISIS PENERAPAN SISTEM E-COMMERCE PADA UMKM (Studi Kasus: Warung Nasi Goreng Mas No di Jalan Apron Jakarta Pusat) - Febry Dwi Wahyuni; Sukarni Novita Sari (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study takes the title "Analysis of the Application of the E-Commerce System at SMEs (A Case Study at Warung Nasi Goreng Mas No on Jalan Apron, Central Jakarta)". The purpose of this research is to find out and analyze how the E-Commerce system is implemented and whether Grabfood's E-Commerce is more in demand than OVO and Go-Pay at Warung Nasi Goreng Mas No. This research is a descriptive qualitative research. Data were collected using interviews, observation and documentation. The results showed that the application of E-Commerce carried out by Warung Nasi Goreng Mas No fulfilled the E-Commerce components such as being open to the public, services provided according to requests, and simple transactions. In implementing the system Warung Nasi Goreng Mas No used the E-Commerce of busin ess to consumer (B2C) type because it meets the E-Commerce criteria. Based on the data obtained from reports from Grab Indonesia, Go-Biz, and OVO Merchant within 6 months, it is known that Grabfood is more attractive to consumers. So, of the three E-Commerce components implemented at Warung Nasi Goreng Mas No, the one that consumers are most interested in is the Grab application.